Effectiveness of Android-Based Learning Media “7 Minutes Workout” on the Motivation and Activity of Junior High School Students - Tomy Angga Pratama; Waris; Rina Sugiarti Dwi Gita (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines how the "7 Minutes Workout" application affects students' motivation and activity levels at SMP Negeri 1 Semboro, Jember Regency. This study used a quasi-experimental design with a control group and an intervention group. The intervention group used the application for structured exercise, while the control group followed the traditional learning method. Student activity data were collected using ATA (Total Active Activity) and SDE (Effective Duration Session) metrics and analyzed using the Friedman test to identify significant differences across time. The results showed that the application significantly increased motivation and participation in physical activity among students in the intervention group, while the control group showed no increase. These results support the idea of the effectiveness of using ICT learning media on a material that focuses on students' active involvement in learning. This study suggests the use of fitness applications in the curriculum to encourage a healthy and active lifestyle for students.